2021
DOI: 10.51383/ijonmes.2021.95
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Preservice Teachers’ Academic Self-Efficacy and Academic Motivation

Abstract: The purpose of this study is to determine the academic self-efficacy and motivation levels of preservice teachers and to investigate these cognitive aspects in terms of various variables. The participants of the current study consist of 621 preservice teachers studying at Necmettin Erbakan University Ahmet Keleşoğlu Faculty of Education in 2020-2021 academic year. The study adopted a single survey model. Research data were collected using Academic Self-Efficacy Scale and Academic Motivation Scale. Independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
3
9
0
3
Order By: Relevance
“…Our research data confirmed the fact that students were constantly rethinking their professional choice. Although we found low indicators of first-year students' amotivation, which coincides with the data of other researchers (Arslantas, 2021;Hakan and Münire, 2014;Sivrikaya, 2019;Spittle, Jackson and Casey, 2009), amotivation increases significantly in the second year, it also increases in the third year, and remains similar in the fourth year. This change in amotivation may be related to unsatisfactory or different expectations and more experience gained.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our research data confirmed the fact that students were constantly rethinking their professional choice. Although we found low indicators of first-year students' amotivation, which coincides with the data of other researchers (Arslantas, 2021;Hakan and Münire, 2014;Sivrikaya, 2019;Spittle, Jackson and Casey, 2009), amotivation increases significantly in the second year, it also increases in the third year, and remains similar in the fourth year. This change in amotivation may be related to unsatisfactory or different expectations and more experience gained.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that the year of study did not affect changes in students' intrinsic AcM, but it affected extrinsic AcM: the fourth-year students' EM, except for EMintrojected, decreased significantly compared to that of the firstyear students. Sivrikaya (2019) also found that prospective PE teachers' internal AcM did not change during the study period, but some authors (Arslantas, 2021;Brouse et al, 2010;Hakan and Münire, 2014) established decreased fourth-year students' indicators of both IM and EM compared to the ones of the first-year students. However, EM-identified indicators are particularly important when analysing students' professional expectations, as they directly reflect how students perceive the value of higher education for their vocational choice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The concept of motivation has a critical importance in ensuring a sustainable success in schools. The attitude towards the teaching profession is important in terms of its impact on the processes during the practice of the profession The motivation status of teachers regarding their profession is closely related to their commitment to their profession (Arslantaş, 2021). In addition, the desire to gain prestige in the environment where they live and to make their families happy increases the motivation of teachers regarding the profession.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature especially in recent years, studies on moral disengagement (Boardley and Kavussanu;Çelik, 2022;Detert et al 2008;Erbaş and Şahin-Perçin, 2016;Eroğlu et al 2020;Fitzpatrick and Bussey, 2018;Gencer, 2020;Hacıkeleşoğlu, 2021;Kağan and Yazıcıoğlu, 2021;Karataş et al 2019;Keskin, 2021;Köfünyeli, 2022;Köklü, 2019;Newman et al 2017;Nur, 2019;Özkan, 2019;Parladıcı, 2020;Sayraç-Kavadar, 2021;Turan, 2021;Visconti et al 2015;Yazıcıoğlu, 2020;Yavuz-Birben, 2019), the issue of academic motivation (Alkan and Arslan, 2019;Arslantaş, 2021;Bilgili and Keklik, 2022;Canbay, 2016;Gürlek, 2021;Kıran, 2019;Kiremitci et al 2020;Koca and Dadandı, 2019;Özgenel and Deniz, 2020;Selen, 2022;Taskesen, 2019;Taşkın, 2016;Tezel, 2021;Titrek et al 2018;Yeşiltaş, 2020) and the studies examining the relationship between the two concepts are not at sufficient level. In the current study, studies similar to the subject area content of the research problem were examined in depth.…”
Section: Introductionmentioning
confidence: 99%